Modulation of NMDA receptor currents by adenosine A2A receptors in the Schaffer collaterals-CA1 synapses. - Henriques, Ana Margarida Cardoso (2017)
Dissertação de Mestrado em Biologia Celular e Molecular apresentada à Faculdade de Ciências e Tecnologia